Honeycomb body surface treatment method adopting sacrificial particles
By depositing sacrificial particles on the walls of the porous honeycomb structure and burning them out during heat treatment, the problem of in-depth penetration of filter materials is solved, filtration efficiency is improved and back pressure is reduced.
Patent Information
- Application Number
- CN202380066408.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-30
- Filing Date
- 2023-09-26
- Publication Date
- 2025-04-25
AI Technical Summary
When removing particles in existing porous filters, the filter material easily penetrates deep into the inner pores of the honeycomb wall, resulting in a reduced filtration efficiency and an increase in back pressure.
By depositing sacrificial particles on the walls of the porous honeycomb structure, the second particle is prevented from entering the inner pores of the wall and burning the sacrificial particles in subsequent heat treatment to avoid increasing the load and back pressure of the filter material.
Improves the utilization rate and filtration efficiency of filter materials, reduces back pressure, and reduces production costs.
Smart Images

Figure CN119894585A_ABST
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims the benefit of priority under 35 U.S.C. §119 to U.S. Provisional Application Serial No. 63 / 412013, filed on September 30, 2022, the contents of which are relied upon and incorporated herein by reference in their entirety. background Technical Field
[0004] The present disclosure relates to methods for surface treating porous bodies, such as porous ceramic honeycombs, with sacrificial particles. Background Art
[0005] Wall flow filters are used to remove particulates from a fluid exhaust gas stream (e.g., from an internal combustion engine exhaust). Examples include: diesel particulate filters for removing particulates from diesel engine exhaust and gasoline particulate filters (GPF) for removing particulates from gasoline engine exhaust. The exhaust gas to be filtered enters the inlet channel and exits the filter through the channel walls via the outlet channel, and the particulates are captured on or in the inlet channel walls as the gas traverses and then exits the filter. Summary of the invention
[0006] Aspects of the present disclosure pertain to porous filter bodies and methods of making them, including the use of sacrificial materials.
[0007] In one aspect, the present invention discloses a method for manufacturing an article, which includes: a honeycomb structure extending axially from a first face to a second face, the structure including a plurality of porous walls extending axially and having a surface defining a plurality of axial channels, the walls having internal pores, wherein the surface of the walls includes surface openings leading to at least some of the internal pores, the method including: depositing the first particles on the walls of the honeycomb structure by flowing the first particles into the honeycomb structure so that the first particles and optionally a first suspension of the fluid are axially transferred into the channels, thereby causing the first particles to flow into the honeycomb structure, so that at least some of the first particles are arranged in the surface openings, arranged above the surface openings and / or arranged around the surface openings; after a selected deposition amount of the first particles is deposited in the honeycomb structure, terminating the transfer of the first particles into the channels, wherein the selected deposition amount of the first particles per volume of the honeycomb structure is greater than 0.01 g / L and less than 5.0 g / L, wherein the first particles include sacrificial particles, the sacrificial particles including organic materials, the organic materials including macromolecules, one or more polymers, or a combination thereof.
[0008] The organic material may include protein particles, whey protein particles, collagen peptide particles, or a combination thereof. The organic material may include protein particles having a particle size of less than 10 μm.
[0009] The sacrificial particles may also include calcium and phosphorus.
[0010] The sacrificial particles may also include calcium, phosphorus, sodium and potassium.
[0011] The organic material may include starch.
[0012] Organic materials may include synthetic polymers.
[0013] The organic material may include polystyrene, polyacrylate, oligomer, or a combination thereof.
[0014] The oligomer may include one or more polyolefins having a molecular weight of 5000 Daltons or less.
[0015] The method may also include: after the flow of the first suspension, axially transferring the second particles from the second suspension of the second particles into the channel, thereby depositing the second particles on the wall of the honeycomb structure, wherein the deposited sacrificial particles block at least some of the second particles from entering the internal pores of the wall. In an embodiment, the sacrificial particles block at least most of the second particles from entering the internal pores of the wall. In an embodiment, the sacrificial particles block all of the second particles from entering the internal pores of the wall. In an embodiment, the second particles do not penetrate below the surface of the wall for more than 25% of the lateral thickness of the wall. In an embodiment, the second particles are not arranged below (i.e., do not penetrate) the surface of the wall. The method may also include terminating the transfer of the second particles into the channel after a selected deposition amount of the second particles is deposited in the honeycomb structure, wherein the selected deposition amount of the second particles per volume of the honeycomb structure is greater than 0.01 grams per liter and less than 8.0 grams per liter. In an embodiment, the method also includes terminating the transfer of the second particles when the deposition amount of the second particles per volume of the honeycomb structure ranges from 1.0 to 8.0 grams per liter. In an embodiment, the method further comprises terminating the transfer of the second particles when the deposition amount of the second particles per volume of the honeycomb structure ranges from 2.0 to 7.0 g / L. In an embodiment, the method further comprises terminating the transfer of the second particles when the deposition amount of the second particles per volume of the honeycomb structure ranges from 3.0 to 7.0 g / L. The method may further comprise heating the honeycomb structure one or more times and one or more temperatures sufficient to remove the sacrificial particles or at least some of the sacrificial particles from the honeycomb structure. In an embodiment, during the flow transfer of the first and second suspensions of the first and second particles, at least some of the axial channels are blocked, sealed, or plugged, thereby inducing the carrier fluid to pass through one or more porous walls of the honeycomb structure from at least one channel to another adjacent channel, thereby inducing particle deposition by filtration.
[0016] The first suspension may include first sacrificial particles and a carrier fluid. The carrier fluid may be gaseous; for example, the carrier fluid may be a gas.
[0017] The majority of the sacrificial particles are preferably arranged in the portion of the internal pores of the wall having surface openings leading to the passages for the transfer of the first particles.
[0018] In an embodiment, a majority of the sacrificial particles do not penetrate more than 50% of the lateral thickness of the wall below the surface of the wall.
[0019] In an embodiment, after deposition, the sacrificial particles are not disposed below the surface of the walls defining the open pores at the surface, that is, the sacrificial particles have not penetrated into the internal porosity of the walls.
[0020] In embodiments, at least some of the sacrificial particles bridge across at least some of the surface openings.
[0021] In an embodiment, the deposition amount of the first particles per volume of the honeycomb structure ranges from 0.1 to 5.0 g / L.
[0022] In an embodiment, the deposition amount of the first particles per volume of the honeycomb structure is less than 4.0 g / L.
[0023] In an embodiment, the deposition amount of the first particles per volume of the honeycomb structure is less than 3.0 g / L.
[0024] In an embodiment, the deposition amount of the first particles per volume of the honeycomb structure is less than 2.0 g / L.
[0025] In an embodiment, the deposition amount of the first particles per volume of the honeycomb structure is 0.1 to 3.0 g / L.
[0026] In an embodiment, the deposition amount of the first particles per volume of the honeycomb structure is 0.1 to 2.0 g / L.
[0027] In an embodiment, the deposition amount of the first particles per volume of the honeycomb structure is 0.1 to 1.5 g / L.
[0028] In an embodiment, the sacrificial particles have a particle size range of 0.1 to 4 μm.
[0029] In an embodiment, the sacrificial particles have a particle size range of 0.5 to 4 μm.
[0030] In an embodiment, the sacrificial particles have a median particle size of 0.1 to 3 μm.
[0031] In an embodiment, the sacrificial particles have a median particle size of 200 to 600 μm.
[0032] The second particles may comprise a primary particle size in the range of 0.1 to 1 μm when in suspension prior to spraying.
[0033] In an embodiment, the sacrificial particles comprise a secondary particle size in the range of 0.1 to 5 μm after spraying and / or after deposition.
[0034] In an embodiment, the second particles comprise a primary particle size in the range of 0.1 to 1 μm when in suspension before spraying and a secondary particle size in the range of 0.1 to 5 μm after spraying and / or after deposition.
[0035] The first suspension may include one or more liquids that are prevented from contacting the article by, for example, heating and / or evaporation or other removal. Prior to contacting the article, the flow of first particles may be maintained at one or more temperatures in the range of 110-160C.
[0036] The porous wall may have a surface porosity of 35% to 75%.
[0037] The porous walls may have a median pore size of 5 to 50 microns.
[0038] The porous walls may have a median pore size of 5 to 30 microns.
[0039] The porous walls may have a median pore size of 10 to 30 microns.
[0040] The loading of sacrificial particles (eg, protein particles) is preferably in the range of 0.1-2.0 g / L (grams per overall external dimension volume of the honeycomb).
[0041] Additional features and advantages are set forth in the following detailed description, and in part will be apparent to those skilled in the art from that description or may be learned by practicing the embodiments described herein, including the following detailed description, claims, and accompanying drawings.
[0042] It should be understood that both the foregoing general description and the following detailed description describe various embodiments and are intended to provide an overall review or framework for understanding the nature and characteristics of the claimed subject matter. The included drawings provide a further understanding of the various embodiments, and the drawings are incorporated into and constitute a part of this specification. The drawings illustrate the various embodiments described herein and, together with the description, are used to explain the principles and operation of the claimed subject matter. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 An embodiment of the method disclosed herein is schematically shown, showing three steps: (1) depositing a sacrificial material (first particles) (SL); (2) depositing a filter material (second particles), such as alumina agglomerates and / or aggregates thereof; and (3) burning off the sacrificial material (first particles) during a heat treatment process.
[0044] Figure 2A and 2B There is no sacrificial material ( Figure 2A ) and having a sacrificial material according to the present disclosure ( Figure 2B ) cross-sectional SEM images (perpendicular to the longitudinal or axial axis of the honeycomb structure and parallel to the pores and their channels) of two particulate filter bodies manufactured using the same method.
[0045] Figure 3 is a SEM photograph of the surface of the above filter body after deposition of 5 g of skim milk protein particles according to the present disclosure.
[0046] Figure 4 Shown is the milk protein particle size distribution of skim milk using the Nanotrac Wave after three runs on the three substrate filter bodies herein.
[0047] Figure 5 The graph shows the FE loss after water resistance test for the skim milk pre-treated example and the example without skim milk pre-treatment. After each extremely high FE (99%), the filter body examples were heat treated by each of three heat treatments: 200C, 485C, 600C.
[0048] Figure 6 The graph shows the FE loss after water resistance test for the skim milk pre-treated example and the example without skim milk pre-treatment. After each very high FE (96%), the filter body examples were heat treated by each of three heat treatments: 200C, 485C, 600C.
[0049] Fig. 7A The effect of skim milk pre-treatment on the filtration performance of a very high FE (96%) filter body with filter material (freshly deposited) is graphically shown and for Example Group 4 the dependence of the FE on the filter material loading is shown.
[0050] Figure 7B The effect of skim milk pretreatment on the filtration performance of a very high FE (96%) filter body with filter material (freshly deposited) is graphically shown, and for example set 4 the dependence of the FE on the pressure dP is shown.
[0051] Fig. 8A The graph shows the relationship between the filtration efficiency and the filter material loading on the filter body after heat treatment at 485C for various sacrificial loadings.
[0052] Figure 8B The graph shows that for various sacrificial loads, after heat treatment at 485°C, Fig. 8A The relationship between the filtration efficiency and the filter pressure drop on the filter body.
[0053] Fig. 9Shown is the clean state FE loss of the examples after water saturation testing (which is after 650C / 9h heat treatment).
[0054] Fig.10 Shown are the protein particle size distributions for skim milk, milk powder and Isopure protein particles for the examples herein.
[0055] Fig.11A and 11B SEM images showing the surface morphology of the honeycomb walls of the Examples preconditioned with sacrificial material.
[0056] Fig. 12A and 12B SEM images of branched Isopure protein particles and skim milk protein particles, which have different shapes and morphologies but have a similar size range of 0.5-4 microns, are shown respectively.
[0057] Fig.13A Schematic showing post-water FE loss of a very high (about 99%) FE pre-conditioned filter body with filter material.
[0058] Fig. 13B Schematic showing the post-water FE loss of a very high (about 96%) FE pre-conditioned filter body with filter material portion (non-pre-conditioned filter portion with inorganic deposits).
[0059] Fig.14 SEM image of collagen peptide particles showing the surface morphology of the pre-conditioned filter body.
[0060] Fig.15 SEM image showing the branched collagen protein particles in the as-sprayed state. Their shape and morphology are different from the Isopure protein particles and skimmed milk powder protein particles, but their size is similarly in the range of 0.5-4 microns.
[0061] Fig.16 The FE loss after water saturation testing is shown for various Examples herein pre-conditioned with sacrificial materials, which is the difference in FE before and after water saturation testing.
[0062] Fig.17 Exemplary steps of an aerosol deposition process that may deposit sacrificial material and / or filter material onto a filter body are schematically shown.
[0063] Fig.18 An exemplary apparatus for forming a honeycomb body is shown schematically.
[0064] Fig.19The filter body (unplugged) is schematically shown and comprises a plurality of intersecting walls defining a plurality of internal channels, with the matrix surrounded by a peripheral wall.
[0065] Fig. 20 A plugged filter body is schematically shown comprising a plurality of intersecting walls defining a plurality of internal channels, some of the channels being plugged at each end, the matrix being surrounded by a peripheral wall.
[0066] Fig.21 Schematically shown is an axial cross-section of a plugged filter body comprising a plurality of intersecting walls defining a plurality of internal channels, some of the channels being plugged at each end, the matrix being surrounded by a peripheral wall, the plugging pattern forcing flow from the inlet channel through the porous wall to the outlet channel as indicated by the arrows. DETAILED DESCRIPTION
[0067] Reference will now be made specifically to embodiments of methods for forming a honeycomb body, the honeycomb body comprising a porous honeycomb body including deposits on or in or both porous ceramic walls of a honeycomb matrix, embodiments of which are shown in the accompanying drawings. In embodiments, the honeycomb matrix is a honeycomb structure, such as a monolithic honeycomb, for example: produced by extrusion through a honeycomb die; or in other embodiments, the honeycomb matrix includes blocks or segments of two or more honeycomb matrices, which are contained or bonded together by, for example, an adhesive. The deposits may include materials deposited into the honeycomb body and compounds that may be formed, for example, by heating one or more of the deposited materials. For example, a binder material may be converted by heating to an organic component that is ultimately burned off or volatilized, while an inorganic component (e.g., silicon oxide) remains in the honeycomb filter body. One or more types of deposits may be used as sacrificial deposits, or even sacrificial layers. Whenever possible, the same reference numerals will be used throughout the drawings to represent the same or similar components.
[0068] definition
[0069] As used in this specification and the appended claims, the singular forms "a," "an," and "the" include embodiments having plural referents unless the context clearly dictates otherwise. As used in this specification and the appended claims, the term "or" is generally employed in its sense including "and / or" unless the context clearly dictates otherwise.
[0070] As used herein, "having," "including," "comprising," "includes," or "including," are used in their open forms and generally mean "including, but not limited to."
[0071] "Honeycomb" as referred to herein includes a ceramic honeycomb structure having a matrix of intersecting walls forming pores defining channels. The ceramic honeycomb structure may be formed, extruded or molded from a plasticized ceramic or a batch mixture or paste forming the ceramic. The honeycomb may include a peripheral wall or skin that is extruded with the matrix of the wall or applied after the matrix is extruded. For example, the honeycomb may be a plugged ceramic honeycomb structure that forms a filter body comprising cordierite or other suitable ceramic material. A plugged honeycomb has one or more channels blocked at one or both ends of the body.
[0072] The honeycomb disclosed herein includes a ceramic honeycomb structure including at least one wall supporting one or more particulate deposits, for example, which can be configured to filter particulate matter from a gas flow. The deposits can be in discrete areas or in some portions, or some embodiments can form one or more layers of deposited material at a given location on the wall of the honeycomb. The deposits according to some embodiments include: inorganic materials; in some embodiments, organic materials; and in some embodiments, both organic and inorganic materials. For example, in one or more embodiments, the honeycomb structure of the honeycomb can be formed from cordierite or other porous ceramic materials, and also includes material deposits arranged on or below the wall surface of the cordierite honeycomb structure.
[0073] In some embodiments, the second deposited material type includes one or more inorganic materials, such as one or more ceramic or refractory materials.
[0074] As used herein, "green" or "green ceramic" are used interchangeably and refer to unsintered or unfired material unless otherwise specified.
[0075] The methods disclosed herein can be used to apply surface treatments to articles (e.g., articles comprising porous walls, such as filters or particulate filters), which can provide improvements in the filtration effect or filtration efficiency of particulate filters (e.g., filters comprising bare honeycomb bodies, or filters comprising honeycomb bodies on or in which other materials (e.g., filter material deposits, layers, membranes and / or catalytic materials) are deposited).
[0076] The methods disclosed herein can be used to add sacrificial deposits to the surface of the porous wall of a particulate filter, such as preparing the particulate filter for further surface treatment by additional deposits similar to filter deposits, such as those containing one or more types of inorganic particles. In an embodiment, the methods disclosed herein can help achieve high filtration efficiency (FE) and low back pressure (dP) of a particulate filter (e.g., a gasoline particulate filter) at the same time. In an embodiment, a pre-conditioning method for a porous honeycomb body (e.g., a porous honeycomb body containing a porous ceramic honeycomb structure, such as a honeycomb body (including, for example, a bare honeycomb body that has not yet received other filter deposits)) with a sacrificial layer is disclosed herein. For a given amount of filter deposits or inorganic deposits, loads, it is found that the particulate filter body can exhibit improved filtration efficiency by using a sacrificial layer deposition before depositing those filter deposits. That is, when first treated with a sacrificial deposit as described herein, a higher filtration efficiency can be obtained at the same inorganic surface treatment load. A lower back pressure can be additionally obtained after, for example, the sacrificial layer is burned off by heat treatment or heat treatment or curing. In various embodiments, such a surface-treated particulate filter is suitable for filtering particulate matter (e.g., carbonaceous soot (e.g., ash)) contained in the exhaust gas of a lean-burn gasoline direct injection (GDI) engine, that is, for example, a gasoline particulate filter (GPF) having a honeycomb structure is used to collect particulate matter in the exhaust gas of a vehicle equipped with a GDI engine.
[0077] One approach to making a suitable GPF with high clean filtration efficiency is to deposit a porous layer of a filter deposit or inorganic material on the wall surface of the honeycomb matrix of the substrate (uncoated or undeposited) GPF. In various embodiments, an ethanol-based aerosol deposition process can be used, in which a stream of agglomerated alumina particles is generated by passing an ethanol-based alumina slurry through a nozzle or multiple nozzles. The freshly deposited filter material or, in various embodiments, the freshly deposited layer includes an aggregate of alumina spherical agglomerates ranging in size from submicron to several microns. In such embodiments, it was found that during initial deposition, some fine agglomerates would penetrate and be captured inside the pores of the substrate wall or even slide through the pores.
[0078] It was found that the increase in the filter material loading can be achieved by longer processing time and / or providing a honeycomb structure with porous walls having smaller pore diameters to achieve a thicker and / or tighter porous layer on the honeycomb wall; however, such a scheme may result in the defect of increasing the pressure drop (increase in back pressure) on the filter, in some cases, significantly higher. In an embodiment, the method disclosed herein includes: depositing a sacrificial layer before depositing the filter material (e.g., comprising an anode material), and then removing the sacrificial material, for example, during the curing process, which helps to avoid increasing (and in some cases reducing) the filter material loading on the particle filter, and helps to reduce the filter material loading and helps to avoid increasing (and in some cases reducing) the back pressure, especially for high FE GPF products. The method disclosed herein also preferably minimizes and even more preferably avoids filling the pores of the walls of the honeycomb matrix with sacrificial materials and with filter material deposits. Thus, a sacrificial layer, for example, a layer of protein particles from skim milk, can be applied to a bare honeycomb body before depositing the filter material, and in various embodiments, the same deposition equipment and process are preferably used for the sacrificial material and for the filter material, for example: an aerosol atomization spray process with the same processing window. In embodiments, spraying skim milk and alumina suspension in the same manner or even in the same chamber can simplify the process and make production more practical and cost-effective. Thus, for example, a sacrificial layer (e.g., a sacrificial protein layer) can function as a barrier layer to help reduce or even avoid the penetration (or sliding) of filter material (e.g., alumina aggregates and agglomerates) deep into the pores of the walls of the honeycomb matrix, especially at the beginning of the deposition process of the filter material, so that in some embodiments, better filter material utilization and ultimately higher filtration efficiency of the particulate filter can be achieved, such as by applying less filter material (lower filter material loading) while still being able to achieve higher filtration efficiency, and preferably, lower filter material loading means shorter deposition time, which leads to lower production costs. The sacrificial material can then be burned off during a subsequent curing or heat treatment process, such as heating the honeycomb to 485C for 1 hour.
[0079] Figure 1An embodiment of the method disclosed herein is schematically shown, showing three steps: (1) depositing a sacrificial material (SL); (2) depositing a filter material, such as alumina agglomerates and / or aggregates thereof; and (3) burning off the sacrificial material during a heat treatment process. The sacrificial material acts as a barrier to particles that penetrate deep into the pores of the walls of the honeycomb matrix defining the channels or slide through the pores. The sacrificial barrier deposit is particularly useful in the beginning or early stages of the deposition of the filter material. Preferably, a majority of the first particles (or sacrificial particles) are deposited into the pores of the surface of the honeycomb wall facing the channels, which enables the second particles (e.g., alumina particles) to have a certain degree of physical contact with the honeycomb wall, which may be beneficial for thermal FE stability and water durability. It was found that when a high protein loading (sacrificial particles) was applied, the FE loss after heat treatment was higher, as demonstrated in the examples herein. Shallow penetration of sacrificial particles is preferred, but in some embodiments, deep penetration of sacrificial particles is acceptable.
[0080] Figure 2A and 2B There is no sacrificial material ( Figure 2A ) and with sacrificial materials ( Figure 2B ) cross-sectional SEM images (perpendicular to the longitudinal or axial axis of the honeycomb structure and parallel to the pores and their channels) of two particulate filter bodies made by Figure 2A As can be seen in Figure 2, for the case without sacrificial material, deep bed penetration of the filter material (here alumina agglomerates) is observed, including at the beginning of the filter material deposition, while a much smaller penetration is observed on the honeycomb with sacrificial material, as shown in Figure 2. Figure 2B As shown. It was found that less filter material penetration leads to better filter material utilization, and leads to higher FE efficiency; that is, it was found that less filter material loading is needed to achieve the target FE. In addition, less filter material loading means shorter deposition time and thus lower production cost. During the subsequent curing or heat treatment process (e.g., 485C heating), the sacrificial material can be burned off, thus leading to a significant drop in back pressure in the final particulate filter.
[0081] The preconditioning process for depositing the sacrificial material can be carried out in several ways, for example by various coating processes. For filter materials deposited by osmosis, in which the filter material is transferred to the filter body by a spraying process, it is preferred to use the same spraying process for the sacrificial material. For example, spraying the alumina suspension and spraying skim milk in the same way or even in the same chamber can make the process simpler, more practical and / or more cost-effective. It was found that such spraying of skim milk exhibited significantly shorter processing times, much higher FE per sacrificial material (protein) load, and less demand, compared to, for example, the soaking method disclosed in US7,767,256.
[0082] In various embodiments, the spray deposition mixing chamber temperature range may be 110-160°C. The skim milk flow rate range may be 4-36 g / min. The atomizing gas flow rate may be 5-20 Nm m 3 / hour. Drying gas flow rate can be 40-100Nmm 3 / hour. An example of an apparatus having a spray deposition mixing chamber is described below.
[0083] As a starting component for example herein, a filter body is used as a substrate honeycomb filter body ("substrate filter body"), which would be suitable for use in a gasoline particulate filter, a filter body is prepared which consists essentially of a cordierite honeycomb structure comprising a matrix of interconnected porous ceramic walls having a bulk porosity of 55%, the walls forming a plurality of channels which are blocked in various ways at either the inlet and / or outlet ends so that the incoming gas is forced to flow from the inlet channel through the porous ceramic walls to the outlet channel. The filter body has an outer diameter of 4.252 inches and an axial length of 4.724 inches. A sacrificial material in the form of 5 g of skim milk protein particles is deposited onto the surface of the wall defining the inlet channel of the filter body. The protein particles having a particle size of 0.2-10 microns land around the holes on the wall surface, thereby partially or completely blocking the hole entrances at the surface of the substrate wall. It was observed that even more skim milk protein particles were applied to completely cover the holes. The amount of skim milk protein particles is an important parameter, and the target amount of protein particles applied on the surface of the wall prior to deposition of additional filter material is selected as described below, which can simultaneously provide filtration efficiency (FE) and minimize backpressure penalty, and even reduce engine operating backpressure, relative to a comparative gasoline particulate filter that does not benefit from the use of sacrificial material. It was found that if the amount of protein particles is too low, the improvement in filtration efficiency and / or backpressure management may be limited, while if the amount of protein particles is too high, significant filtration efficiency degradation (e.g., due to heat treatment) may occur.
[0084] Figure 3 is a SEM photograph of the surface of the above filter body after deposition of 5 g of skim milk protein particles.
[0085] After preconditioning the bare honeycomb by deposition of protein particles (e.g., by an aerosol spray deposition process), one or more filter materials are deposited onto the surface of the same wall surface such that at least some, or in some cases all, of the filter material is deposited on top of the sacrificial layer. The filter material may be applied by a filtration process using, for example, an aerosol spray deposition process. The two spray processes may be performed in the same spray chamber or in separate spray chambers.
[0086] It was found that in general, the greater the amount of protein particles applied, the greater the FE improvement observed in the filter body in the clean state (or just deposited state) before the filter is used to clean engine exhaust. In addition, the greater the amount of protein particles applied, the higher the back pressure that may occur. Thus, skim milk protein particle pretreatment can lead to higher FE after deposition of the filter material. Another application is that the filter material loading required to achieve the same FE in the finished filter product is lower.
[0087] In addition, greater FE increases can be obtained on bare components (before any deposition) with lower initial filtration efficiencies. For example, spraying the same amount of 10 g of skim milk protein particles on the inner honeycomb wall surface of a substrate filter body having the same dimensions as in the above example (4.252 inches by 4.724 inches) before applying the same amount of filter material increased the as-deposited FE of such GPF component by 1.8% from 96.3% to 98.1, but there was only a 0.1% FE improvement for such GPF component from 99.2% to 99.3%.
[0088] After the filter material is deposited, a heat treatment can be applied to solidify the filter material and to burn off the sacrificial material. The heat treatment temperature (multiple heat treatment temperatures) may include: greater than 200C, greater than 300C, or greater than 400C, which may depend on the type or amount of the sacrificial material used. Generally speaking, most of the sacrificial material should be decomposed or burned off, preferably a weight loss of >80% of the amount of sacrificial material initially deposited on the filter body. It was found that after the filter material was deposited and the sacrificial material was removed, the filter body exhibited a lower pressure drop than a similar filter body that was not pre-conditioned by the sacrificial material. The filtration efficiency may depend on the quantity (amount) and morphology of the sacrificial material. Generally speaking, the greater the amount of sacrificial material applied, the more pressure drop dP reduction can be achieved, but more FE losses may occur due to heat treatment. As shown in the example below, a pre-conditioning process using a sacrificial material can provide both FE improvement and pressure drop reduction.
[0089] Example Group 1: Skim milk pretreatment process: spraying vs. soaking
[0090] In this set, the substrate filter bodies described above were pre-conditioned with skim milk by two methods: (a) spraying and (b) soaking or immersion. Figure 4Shown is the protein particle size distribution of skim milk using Nanotrac Wave. Three particle size distribution runs were performed on value skim milk purchased from Walmart in July, August and September. The protein particle size range was 72-486nm with average d50 = 210.6, 215.5 and 209.7nm respectively. The solids concentration in the skim milk was approximately 9.4%, measured by loss on drying at 115C for 20 minutes.
[0091] The protein particle spraying process was carried out on the same equipment as the filter material was deposited on the filter body, and the amount or quantity of skim milk deposited on the filter body in this subgroup ranged from 5 to 15 g. The fixed spraying conditions applied included: a mixing chamber temperature of 140°C, a protein particle liquid flow rate of 12 g / min, a 60 Nm m 3 / h nitrogen dry carrier gas flow rate, and 10 Nm m 3 The skim milk was atomized with a nitrogen atomizing gas flow rate of 1 / h. The spraying time ranged from 25 to 75 seconds using the same nozzle as the filter material.
[0092] The protein particle soaking process comprises two steps: soaking and drying.Before soaking, the bare substrate filter body is wrapped with polytetrafluoroethylene strips to prevent the protein in the skim milk from directly contacting the outside of the porous substrate.After soaking in the skim milk of the prescribed amount for 20 seconds, the polytetrafluoroethylene strips are removed from the substrate.The pretreated filter body is dried for about 5 hours in ambient conditions, and then moved into a 60C baking oven and allowed to dry there for 14 hours to prepare for the deposition of filter material.In this subgroup, the soaking of the bare filter body uses 150g, 250g and 500g of skim milk respectively.
[0093] Table 1 shows the protein load in the dried preconditioned filter bodies made by the two different processes described above and the filtration efficiency exhibited via the so-called smoke FE test, which is able to evaluate the filtration efficiency (even when the filter body is in a clean state). As shown in Table 1, spraying 5g to 15g skim milk resulted in an increase in protein load from 0.55 to 1.27g / L, and an increase in smoke FE from 52.5% to 72.3%. In contrast, soaking 150g to 500g skim milk resulted in an increase in protein load from 13.41 to 19.13g / L, but the smoke FE did not change much and was roughly in the low range of 30%. This soaking process, as described in US 7,767,256, was found not to be an efficient process for forming a barrier layer or sacrificial layer.
[0094] Table 1: Comparison of protein loading in dried preconditioned substrates manufactured by two different processes and their smoke FE results
[0095] Sample No. Pretreatment process Skim milk, g Protein loading, g / L Flue gas FE 1 spray 15 1.28 72.4% 2 spray 15 1.27 72.3% 3 spray 10 0.9 63.9% 4 spray 10 0.9 63.6% 5 spray 5 0.52 50.7% 6 spray 5 0.58 54.3% 7 soak 500 20.11 29.8% 8 soak 500 18.26 30.6% 9 soak 250 17.03 29.5% 10 soak 250 16.66 30.2% 11 soak 150 13.38 30.0% 12 soak 150 13.45 33.0%
[0096] Example Group 2: Very high FE filter body (FE about 99%)
[0097] In this group, six (6) substrate filter bodies were treated with different amounts of skim milk (purchased from Wal-Mart's Value Store) using the same spraying process as used for the filter material, 2 filter bodies with 5 g skim milk, 2 filter bodies with 10 g skim milk, and 2 filter bodies with 15 g skim milk. The skim milk spraying parameters were fixed as follows: 140C mixing chamber temperature, 12 g / min liquid flow rate, 60 Nm 3 / h nitrogen dry carrier gas flow rate, and 10 Nm m 3 The skim milk was atomized with a nitrogen atomizing gas flow rate of 1.5 t / h. Each pretreated filter body was returned to the spray chamber and 70 g of alumina suspension was atomized and mixed with the carrier gas and delivered to the filter body using the same spray parameters as the filter material. The alumina suspension was an Almatis suspension in ethanol (11% Almatis-1.33% TEA-1% Triblock-15% 2405 Dowsil). Two (2) additional filter bodies without skim milk pretreatment were also prepared for comparison.
[0098] After the filter material was deposited, the filter bodies were heat treated and evaluated via the following heat treatment sequence: 1) 200C for 1 hour followed by water saturation testing; 2) 485C for 12 minutes followed by water saturation testing; and 3) 650C for 5 hours followed by water saturation testing.
[0099] For the filter bodies in this group, the filter material loading provided very high clean state filtration efficiencies (>90%), even for the examples not pretreated with skim milk. Skim milk pretreatment resulted in significantly lower pressure drop but limited improvement in FE; FE increased with increasing filter material loading, but after FE reached very high values in the range of 98-99%, the improvement in FE flattened out and showed little increase.
[0100] Table 2 shows the FE and dP of examples after deposition of the same amount of filter material (both without milk pretreatment and with various amounts of skim milk pretreatment), immediately after deposition without heat treatment ("as deposited") and after treatment at various temperatures: 200C for 1 hour, 485C for 12 minutes, and 650C for 5 hours.
[0101] Table 2
[0102]
[0103]
[0104] The examples pretreated with 5g skim milk in Table 2 showed similar just deposited FE and pressure drop dP, and the examples pretreated with 10g and 15g skim milk showed slightly higher just deposited FE and dP than the examples not pretreated with skim milk. After exposure to the curing temperature of 200C / 1 hour, the FE and dP changed a little. The heat treatments at 485C and 650C resulted in a slight decrease in FE but the FE was still maintained at a very high level of 99% or higher (except for the examples pretreated with 15g skim milk, which showed the largest drop to 98.6-98.7%). On the other hand, a significant dP drop was observed for the examples treated with skim milk, especially when more skim milk was applied (e.g., 10g and 15g). After the heat treatment at 485C / 12 minutes, the examples treated with skim milk showed lower dP than the examples without pretreatment: 2.0%, 8.0% and 10.1% for the 5g, 10g and 15g milk treatments, respectively. After 650C / 5h heat treatment, the skim milk treated examples exhibited lower dP compared to the examples without pre-treatment: 2.4%, 7.4% and 12.1% for the 5g, 10g and 15g milk treatments, respectively.
[0105] It was found that pre-conditioning the filter body with skim milk resulted in improvements in FE and dP, which would depend on the amount of skim milk spray applied to the filter body. Compared to the unpretreated example, after 650C / 5 hours treatment, the 5g milk pre-treated example exhibited 0.1% higher FE and 2.4% lower dP. The 10g milk treated example exhibited 7.4% lower dP while maintaining the same FE = 99.0%. The 15g milk treated example exhibited 12.1% lower dP but 0.3% lower FE.
[0106] Water saturation resistance can be a challenging requirement for filters that are strengthened by filter material deposits. Skim milk pretreatment was found to have no negative impact on water resistance performance.
[0107] Figure 5Graph showing the FE drop ("FE loss") of the heat treated examples due to water saturation testing. The 200C cured examples showed very good water resistance with less than 0.1% FE loss. After 485C heat treatment, the 15g milk pre-treated examples exhibited slightly higher post-water FE loss. After 650 / 5 hour heat treatment, the milk pre-treated examples exhibited slightly better water resistance, 0.4-0.5% FE loss; compared to 0.6-0.8% FE loss for the non-pretreated examples. The average total FE loss after the above three sequential heat treatment cycles and water saturation testing was: 0.9% for the untreated example; 0.5% for the 5g milk example; 0.8% for the 10g milk example; and 1.2% for the 15g milk example.
[0108] Example Group 3: Very High FE Filter Body (FE about 96%)
[0109] This set of examples focuses on the skim milk pretreatment process and the resulting improvement in filter performance for a filter body having a filter material deposit providing approximately 96% FE. In this example, six (6) substrate filter bodies were treated with different amounts of skim milk by an aerosol spray process: 2 cases with 5 g skim milk, 2 cases with 10 g skim milk, and 2 cases with 15 g skim milk. The skim milk spray parameters were fixed as follows: 140C mixing chamber temperature, 12 g / min liquid flow rate, 60 Nm m 3 / h nitrogen dry carrier gas flow rate, and 10 Nm m 3 / hour nitrogen atomizing gas flow rate. Each pretreated example was then returned to the spray chamber and a fixed totalizer of 37 g of alumina suspension was applied using the same spray parameters. The alumina suspension was an ethanol-based Almatis suspension (11% Almatis-1.33% TEA-1% Triblock-15% 2405 Dowsil). Two additional examples without skim milk pretreatment were also prepared for comparison.
[0110] After final deposition of the filter material, the examples were heat treated and evaluated via the following sequence: 1) 200C for 1 hour followed by water saturation testing; 2) 485C for 12 minutes followed by water saturation testing; and 3) 650C for 5 hours followed by water saturation testing.
[0111] It was found that for the 96% clean FE example, skim milk pretreatment could improve FE and reduce back pressure simultaneously.
[0112] Table 3 shows the FE and dP of the examples with the filter material as deposited and after heat treatment at 200C / 1 hour, 485C / 12 minutes and 650C / 5 hours. After the filter material is deposited, the examples pretreated with skim milk show an improvement in FE compared to the examples without pretreatment. The greater the amount of skim milk sprayed, the higher the FE as deposited, although the pretreated examples have a higher pressure drop. For all examples, curing at 200C / 1 hour resulted in a slight FE drop in the range of 0.2-0.3%, so the pretreated examples maintained a higher FE but also showed a higher dP.
[0113] After 485C / 12 minutes heat treatment, the pretreated examples maintained 1.2-1.7% higher FE and their pressure drop dP values were close to or lower than those of the non-pretreated examples due to the burning off of skim milk protein particles. The 5g milk pretreated example had 1.4% higher FE and 0.9% higher dP. The 10g milk pretreated example had 1.7% higher FE and 0.1% lower dP, and the 15g milk pretreated example had 1.2% higher FE and 5.1% lower dP.
[0114] Further heat treatment at 650C for 5 hours helped reduce the dP of the milk pretreated examples, but also slightly reduced the FE improvement. The 10g milk pretreated parts had 0.7% higher FE and 0.9% lower dP compared to the unpretreated examples. The 15g milk pretreated parts exhibited 6.4% lower dP but 0.9% lower FE.
[0115] Table 3 shows the FE and dP of the examples without milk pretreatment and the examples with skim milk pretreatment after filter material deposition and heat treatment at different temperatures.
[0116] Table 3
[0117]
[0118] Water saturation resistance can be the most challenging property to achieve for a filter body with deposited filter material. It was found that skim milk pre-treatment had no negative impact on water resistance for those examples, and surprisingly appeared to be beneficial for water resistance after 650C / 5 hours heat treatment, as shown in Figure 2. Figure 6 shown.
[0119] The 200C cured parts exhibited similar good water resistance. After 485C heat treatment, the milk pretreated parts exhibited slightly higher post-water FE loss. After 650 / 5 hours heat treatment, the milk pretreated parts exhibited significantly better water resistance, less than 5% FE loss; while the untreated examples lost 15-20% FE after water saturation. The average total FE loss after these three heat treatment cycles and water saturation tests was: 20.4% for the untreated example; 6.9% for the 5g milk pretreated example; 5.6% for the 10g milk pretreated example; and 7.8% for the 15g milk pretreated example. The pretreated examples of Example Group 3 exhibited much higher total FE loss than the examples of Example Group 2 above.
[0120] Example Set 4: Effect of liquid flow rate during skim milk spraying on the performance of filter components with inorganic deposits.
[0121] This example set focuses on the effect of liquid flow rate on filtration performance during skim milk spraying. The substrate filter body was used as above. Table 4 lists three variables: milk flow rate (6, 12, 24 g / min), milk load (5, 10, 15 g), and filter material load (70, 80 g). Two examples without skim milk pretreatment were also manufactured for comparison. Fixed skim milk spraying parameters included: mixing chamber temperature of 140C, 60 Nm m 3 / h nitrogen dry carrier gas flow rate, and 10 Nm m 3 / hour nitrogen atomizing gas flow rate. Fixed filter material deposition parameters include: 140C mixing chamber temperature, 12g / min liquid flow rate, 60Nmm 3 / h nitrogen dry carrier gas flow rate, and 10 Nm m 3 / hour nitrogen nebulizing gas flow rate. Alumina suspension was used to feed the filter material, and an ethanol-based Almatis suspension (11% Almatis-1.33% TEA-1% Triblock-15% 2405 Dowsil) was used.
[0122] After filter material deposition, the examples were heat treated at 485C for 12 minutes before flue gas FE and dP measurements, and then at 650C for 9 hours before water saturation testing.
[0123] Table 4
[0124]
[0125]
[0126] Fig. 7AThe effect of skim milk pretreatment on the filtration performance of a filter body with filter material (freshly deposited) is graphically shown, and for example set 4 the dependence of FE on the filter material loading is shown.
[0127] Figure 7B The effect of skim milk pretreatment on the filtration performance of a filter body with filter material (freshly deposited) is graphically shown, and for example group 4 the dependence of FE on the pressure dP is shown.
[0128] Figure 7A-7B The effect of skim milk pretreatment on just-deposited filtration performance is shown. For a given amount of deposited filter material (70 g or 80 g), the skim milk pretreated examples show higher filter material loading and just-deposited FE, indicating higher filter material utilization and higher FE efficiency. In addition, the skim milk pretreated examples with 70 g filter material loading show higher FE than the non-pretreated examples with 80 g loading, as shown in Figure 2. Fig. 7A On the other hand, skim milk pretreatment did not significantly affect the FE / dP curve.
[0129] After heat treatment at 485°C for 12 minutes, the skim milk pre-treated examples (especially 15 g skim milk) had higher FE losses. Fig. 8A As shown, for the same filter material loading, the skim milk pretreatment examples show higher FE after 485C (except for the example with 15g cumulative amount of milk). On the other hand, the FE / dP curve of the skim milk pretreatment examples is shifted to the left, indicating a lower dP at the same FE. Lower milk flow rates appear to result in better filtration performance. Example 210602-2A, which was pretreated with 10g milk at a flow rate of 6g / min, showed very good filtration performance (99.15% FE and 226.6Pa pressure drop), compared to the untreated example 210602-17 with FE=98.89% and dP=235.6Pa. Example 210602-5A, which was pretreated with 15g milk at a flow rate of 6g / min, showed FE=98.81% and dP=212.8Pa, which is about 9.7% lower dP than the untreated example.
[0130] Fig. 9 Shown are the flue gas FE losses of the examples after water saturation test (which were after 650C / 9h heat treatment). All examples showed less than 1% FE loss. In the milk pre-treated parts, lower milk flow rates lead to better water resistance.
[0131] Several brands of skim milk were tested and no significant differences in filtration performance were found.
[0132] Other examples were made with other protein particle sources using skim dry milk powder, Isopure protein 100% whey powder, and collagen peptides whey protein.
[0133] Example Group 5: Milk powder and Isopure protein powder as skim milk substitute
[0134] The substrate filter was pre-conditioned using skim dry milk powder and Isopure protein 100% whey powder as described above. Isopure protein powder is whey protein made from water soluble milk protein and contains amino acids.
[0135] First, two pre-conditioned suspensions with a solid loading of 9 wt% were made by adding 9 g of milk powder and Isopure protein powder, respectively, to 91 g of water followed by shaking for a few minutes. The resulting suspensions were stable with no precipitation. Fig.10 The protein particle size distributions for skimmed milk, milk powder and Isopure protein are shown. Skimmed milk powder in water shows a monomodal particle distribution with d50 = 249 nm, while Isopure protein powder in water shows a bimodal particle distribution with d50 = 517 nm.
[0136] In the second step, two groups of bare substrate filter bodies were preconditioned in an aerosol spray chamber by spraying 10 grams of milk powder suspension and Isopure protein suspension, respectively, with the same process parameters as spraying skim milk in Example Group 2. The preconditioned examples had a protein load of 0.74 to 0.84 g / L as shown in Table 1, and a FE range of 60-65%.
[0137] Fig.11A and 11B SEM images showing the surface morphology of the honeycomb wall of the pre-conditioned example. Most of the protein particles landed around the entrances of the pores at the wall surface, partially or completely covering the pores.
[0138] Fig. 12A and 12B SEM images of branched Isopure protein particles and skim milk protein particles, which have different shapes and morphologies but have a similar size range of 0.5-4 microns, are shown respectively.
[0139] In the third step, three bare substrate filter bodies without preconditioning were placed in a spray chamber and sprayed with 80 grams and 43 grams of alumina suspension (11% Almatis-1% TEA-1% Triblock-15% 2405 Dowsil), resulting in freshly deposited FE in the range of 99% and 96%, respectively. Then, all pretreated examples were sprayed with 80 grams or 34 grams of the same alumina suspension, as listed in Table 1 and Table 5. The spraying conditions of the alumina suspension were the same as those of Example Group 2. It was found that for the same filter material delivered through the spray mixing chamber, the filter material load of the pretreated examples on the filter body was higher than that of the non-pretreated examples. For example, after spraying 80 grams of alumina suspension, the filter material loads obtained for the non-pretreated examples and the pretreated examples were 7.63 g / L and 8.18-8.39 g / L, respectively. After spraying 34 grams of alumina suspension on the filter body, the resulting filter material loading was 4.19-4.20 g / L for the non-pretreated and pretreated examples and 4.41-4.46 g / L, respectively. Without being limited to any theory, it is believed that for the pretreated samples, no or less alumina agglomerates slipped through the pores of the filter body and exited through the outlet channel of the filter body because the protein particles covered the pores. After the filter material was deposited, all examples were heat treated at 485°C for 12 minutes before the flue gas FE measurement and dP measurement were performed. Water saturation testing was performed after heat treatment at 650°C for 9 hours.
[0140] Fig. 12A and 12B SEM images showing the surface morphology of filter bodies preconditioned with a) Isopure protein and b) skimmed milk powder protein, respectively.
[0141] Tables 1 and 5 show that all preconditioned filter body components showed both higher as-deposited FE and higher pressure drop dP compared to non-preconditioned components. Much more FE improvement was observed for very high FE filter body components (FE=96%) than for extremely high FE filter body components (FE=99%). After heat treatment at 485°C to burn off milk particles or protein particles, the preconditioned components had 4%-7% lower dP than the non-preconditioned components at the same filter material loading level, while the FE was similar. Further heat treatment at 650°C resulted in 6%-13% lower dP for the preconditioned components.
[0142] Table 1 Table 5: Comparison of FE and dP of control parts (no pretreatment) and pretreated parts after inorganic deposition and 2 heat treatment cycles at different temperatures.
[0143]
[0144] Fig.13A Schematic showing post-water FE loss of a very high (about 99%) FE pre-conditioned filter body with filter material. Fig. 13B Schematic showing the post-water FE loss of a very high (about 96%) FE pre-conditioned filter body with filter material portion (non-pre-conditioned filter portion with inorganic deposits).
[0145] Figures 13A-13B Schematic showing the FE loss after water saturation test, which is the difference in filtration efficiency before and after water saturation test. The preconditioned examples showed similar or slightly lower FE loss, indicating comparable or even better water resistance than the non-preconditioned filter bodies. In general, the very high FE (99%) filter bodies ( Fig.13A ) has a very high FE (96%) filter body ( Fig. 13B ) significantly lower FE loss.
[0146] Experiment #2 Example Group 6: Collagen Powder and Skim Milk
[0147] The bare substrate filter described above was preconditioned with collagen peptides whey protein. Collagen peptides are very small protein fragments from animal collagen. Collagen peptides are made by breaking down whole collagen into smaller fragments.
[0148] First, 9 grams of collagen peptides were mixed with 91 grams of water to form a pre-conditioned suspension with a solid loading of 9% by weight. The resulting suspension was stable without precipitation. The particle size of the suspension was too small to be detected by a light scattering analyzer. In the second step, a group of substrate filter bodies were pre-conditioned in a spray mixing chamber by spraying 10 grams of solution with the same process parameters as the spraying of skim milk in Example Group 2 above. The pre-conditioned amount transferred to the filter body was 10 grams, as shown in Table 2 and Table 6. Measurements after pre-conditioning showed that the protein loading of the components was 0.66 to 0.83 g / L and the FE range was 64-65%.
[0149] Fig.14 SEM image of collagen peptide particles showing the surface morphology of a preconditioned filter body. Most of the protein particles are deposited on the entrance of the substrate pores, partially or completely covering the pores.
[0150] Fig.15 SEM image showing the branched collagen particles in the as-sprayed state. Their shape and morphology are different from the Isopure protein particles and skimmed milk powder protein particles, but their size is similarly in the range of 0.5-4 microns.
[0151] In the third step, another group of bare substrate filter bodies without pre-conditioning were placed in the same spray deposition chamber and sprayed with 80 grams and 45 grams of alumina suspension (11% Almatis-1% TEA-1% Triblock-15% 2405 Dowsil), respectively, resulting in freshly deposited FE in the range of 99% and 96%, respectively. Then, all pre-conditioned filter bodies were sprayed with 80 grams or 34 grams of the same alumina suspension. The amount of filter material transferred was 80 grams or 34 grams, as shown in Table 2 and Table 6. The spraying conditions of the alumina suspension were the same as those of Example Group 2 above. After the filter material was deposited, all filter bodies were heat treated at 485°C for 12 minutes, followed by flue gas FE measurement and dP measurement. Water saturation testing was performed after heat treatment at 650°C for 9 hours.
[0152] Table 2 Table 6: Comparison of FE and dP of control parts (no pretreatment) and pretreated parts after inorganic deposition and 2 heat treatment cycles at different temperatures.
[0153]
[0154] Table 2 Table 6 shows that all preconditioned filter bodies have higher as-deposited FE than non-preconditioned filter bodies, and very high FE filter bodies (FE=96%) with filtered deposits show better FE improvement (about 2%) than very high FE filter bodies (FE=99%) (about 0.24%). All preconditioned filter bodies have higher as-deposited pressure drop dP; however, after burning off the protein at 485°C, at the same filter material transmission level, the preconditioned parts show 4.5-5.7% lower dP than the non-preconditioned parts, while the FE is similar or slightly higher. Further heat treatment at 650°C results in 4.9%-7.7% lower dP for the preconditioned filter bodies.
[0155] Fig.16 The FE loss after the water saturation test is shown, which is the difference in FE before and after the water saturation test. The preconditioned filter bodies showed similar or slightly lower FE losses, indicating similar or even better water resistance. For example, for the same very high FE (FE=96%) group, the non-pretreated samples exhibited FE losses of 2.54% and 2.74%, while the pretreated samples had FE losses of 1.20-1.41%. Overall, the very high FE (99%) proved to have significantly lower FE losses than the very high FE (96%) filter bodies.
[0156] Fig.16 The post-water FE loss of a preconditioned filter component with inorganic deposits was compared to a non-preconditioned filter component with inorganic deposits.
[0157] All pre-conditioned parts showed good water durability with respect to FE loss after 650C / 9 hours heat treatment and water saturation testing, all with less than 1% FE drop.
[0158] Method disclosed herein includes applying material, such as filter material, such as inorganic material, such as ceramic or refractory material, or even porous ceramic or refractory material.In a specific embodiment, filter material is the filter material of aerosol deposition.In some preferred embodiments, filter material includes multiple inorganic particle agglomerates, wherein agglomerates include inorganic (such as ceramic or refractory) material.In some embodiments, agglomerates are porous, thereby can allow gas flow to pass through agglomerates.
[0159] Aerosol deposition can deposit the filter material onto the porous ceramic wall, which can be as small as a single agglomerate or larger (e.g., multiple agglomerates) discrete areas, and in some embodiments, is in the form of a porous layer of filter material on at least some of the surfaces of the walls of the ceramic honeycomb, or in the surface, or both on the surface and in the surface. In certain embodiments, an advantage of the aerosol deposition method according to one or more embodiments is that a ceramic honeycomb with enhanced filtration performance can be produced in an economical and / or more efficient manner.
[0160] In embodiments, the aerosol deposition process disclosed herein includes: preparing a mixture (e.g., an inorganic material, a liquid carrier, and a binder); atomizing the mixture with a nozzle through an atomizing gas to form agglomerates and / or aggregates comprising the inorganic material, the liquid carrier, and the binder (if any); drying the agglomerates and / or aggregates in the presence of a carrier gas or a gaseous carrier stream; depositing the aggregates and / or agglomerates onto a honeycomb; and optionally curing the material. The liquid carrier may include ethanol. In some embodiments, the walls of the apparatus may be heated to assist in drying the aggregates and / or agglomerates.
[0161] In various embodiments, in addition to or in lieu of heating the walls of the device, the carrier gas can be heated so that the liquid carrier can be evaporated from the agglomerates more quickly, which in turn achieves a more efficient generation of agglomerates. The heated gaseous carrier stream carries both the atomized droplets and agglomerates formed by the device and entering the honeycomb body. In some embodiments, the atomizing gas is heated alone or as a combination of heated carrier gases. In some embodiments, aerosolized droplets and / or agglomerates and the gaseous carrier stream co-flow into the chamber of the device in substantially the same manner, which can help reduce material loss or overspray on the walls of the device. In addition, a convergent section can be added to the device before the agglomerates enter the ceramic honeycomb body to help make the gas flow and particle trajectories more uniform in the device. The inner diameter of the end of the convergent section can be slightly larger than the outer diameter of the outer diameter of the ceramic honeycomb body, thereby reducing or eliminating the boundary effects of non-uniform particle deposition.
[0162] In the atomizing nozzle or atomizer, a suspension containing a mixture of a liquid carrier, a binder, and solid particles can be broken up into small droplets, for example, with an average droplet size of 4-6 microns, using high pressure and / or high velocity atomizing gas. The heating of these droplets and the rapid evaporation of the liquid carrier result in the creation of porous inorganic agglomerates as porous inorganic features or structures before being deposited on the honeycomb wall. In some embodiments, more than one nozzle is used, even in some cases the same operating conditions, thereby reducing the liquid flowing through each nozzle and the droplet size can be smaller.
[0163] According to one or more embodiments, the process disclosed herein includes: forming an aerosol with a binder, which is deposited onto a honeycomb, thereby providing a high filtration efficiency material (which may be present in discrete regions and / or portions, or in some embodiments, as an inorganic layer) on the honeycomb, thereby providing a particulate filter.
[0164] According to one or more embodiments, Fig.17 As shown, process 400 includes the steps of mixture preparation 405, atomization to form droplets 410, mixing the droplets with a gaseous carrier stream 415; evaporation of the liquid carrier to form agglomerates 420, depositing the material (e.g., agglomerates) onto the walls of a wall-flow filter 425, and optional post-treatment 430, for example, to cause the material to bond to or into the porous walls of the honeycomb or both. The aerosol deposition method of forming agglomerates containing a binder can provide high mechanical integrity even without any high temperature curing step (e.g., heating to a temperature in excess of 1000°C), and in some embodiments, even higher mechanical integrity after a curing step, such as a high temperature (e.g., heating to a temperature in excess of 1000°C) curing step. Fig.17In the process of aerosol deposition, an inorganic material deposit is formed, which in some embodiments is a porous material deposit. In some embodiments, the material deposit is in the form of discrete areas of filter material. In some embodiments, at least a portion of the material deposit can be in the form of a porous inorganic layer.
[0165] Inorganic particles can be used as raw materials in a mixture to form an inorganic material for deposition. According to one or more embodiments, the particles are oxide or carbide ceramics; in some embodiments, the particles are selected from: Al2O3, SiO2, TiO2, CeO2, ZrO2, SiC, MgO, and combinations thereof. In one or more embodiments, the mixture is a suspension. The particles can be supplied as raw materials suspended in a liquid (e.g., a liquid ethanol carrier), to which other liquid carriers can be optionally added.
[0166] In one or more embodiments, the particles have an average primary particle size in the range of about 10 nm to about 4 microns, about 10 nm to about 3 microns, or about 10 nm to about 2 microns, or about 10 nm to about 900 nm, or about 10 nm to about 600 nm. In specific embodiments, the average primary particle size range is about 100 nm to about 200 nm, for example: 150 nm. The BET surface area of the aerosol particles (which is currently 10 m in some embodiments) can be used to determine the average primary particle size. 2 / g), and the average primary particle size was determined as a calculated value.
[0167] In one or more embodiments, the primary particles include ceramic particles, such as oxide particles, for example: Al2O3, SiO2, MgO, CeO2, ZrO2, CaO, TiO2, cordierite, mullite, SiC, aluminum titanate, and mixtures thereof.
[0168] If necessary, the suspension can be diluted by adding a solvent to form a mixture. If the droplets produced by atomization are of similar size, reducing the solid content in the mixture can proportionally reduce the aggregate size. The solvent should be miscible with the suspension mentioned above and should be a solvent for the binder and other ingredients.
[0169] Binders may be optionally added to strengthen agglomerates and provide stickiness or adhesion, and inorganic binders may be included to provide mechanical integrity to the deposited material. Binders provide bonding strength between particles at elevated temperatures (>500°C). The starting material may be organic. After exposure to high temperatures exceeding about 150°C, the organic starting material decomposes or reacts with moisture and oxygen in the air, and the final deposited material composition may include Al2O3, SiO2, MgO, CeO2, ZrO2, CaO, TiO2, cordierite, mullite, SiC, aluminum titanate, and mixtures thereof. An exemplary binder content range is greater than or equal to 5% to less than or equal to 25%, based on the weight of the particle content. In an embodiment, the binder content is 15 to 20% by weight ± 1%.
[0170] A catalyst may be added to accelerate the curing reaction of the binder. An exemplary catalyst content is 1% by weight of the binder.
[0171] The mixture is atomized into fine droplets by passing a high pressure gas through a nozzle. The atomizing gas contributes to breaking up the liquid-particle-binder stream into droplets.
[0172] In one or more embodiments, liquid-particle-binder droplets are directed into the chamber through a nozzle.
[0173] In one or more embodiments, the liquid-particle-binder droplets are directed into the chamber by a plurality of nozzles. In one or more embodiments, atomization of the plurality of liquid-particle-binder streams is performed by a plurality of atomizing nozzles.
[0174] In an embodiment, the average droplet size according to one or more embodiments can be in the range of 1 micron to 40 microns, including, for example: greater than or equal to 1 micron to less than or equal to 15 microns, greater than or equal to 2 microns to less than or equal to 8 microns, greater than or equal to 4 microns to less than or equal to 8 microns, and greater than or equal to 4 microns to less than or equal to 6 microns, and all values and sub-ranges therebetween. The droplet size can be adjusted by adjusting the surface tension of the mixture, the viscosity of the mixture, the density of the mixture, the gas flow rate, the gas pressure, the liquid flow rate, the liquid pressure, and the nozzle design. In one or more embodiments, the atomizing gas includes nitrogen. In one or more embodiments, the atomizing gas can be substantially composed of an inert gas. In one or more embodiments, the atomizing gas can be primarily one or more inert gases. In one or more embodiments, the atomizing gas can be primarily nitrogen gas. In one or more embodiments, the atomizing gas can be primarily air. In one or more embodiments, the atomizing gas can be substantially composed of nitrogen or air. In one or more embodiments, the atomizing gas can be dry. In one or more embodiments, after entering the chamber, the atomizing gas can be substantially free of liquid carrier.
[0175] The suspension flow rate range is 10 to 40 g / minute, including all values and subranges therebetween, including 18 g / minute.
[0176] Nebulizer gas flow rate Nitrogen flow rate range is 2 to 10 Nm 3 / hour, including all values and sub-ranges therebetween, including 5-6Nm 3 / Hour.
[0177] In one or more embodiments, the suspension comprises: an inorganic material, a liquid carrier and (in some embodiments) a binder, which is supplied to the nozzle as a liquid-particle-binder stream. That is, particles of the inorganic material can be mixed with a liquid carrier and a binder material to form a liquid-particle-binder stream. The liquid-particle-binder stream is atomized into liquid-particle-binder droplets through a nozzle by an atomizing gas. In one or more embodiments, the liquid-particle-binder stream is mixed with an atomizing gas. In one or more embodiments, the liquid-particle-binder stream is directed into an atomizing nozzle, thereby atomizing the particles into liquid-particle-binder droplets. Preferably, the liquid-particle-binder droplets comprise a non-aqueous carrier, a binder material and particles.
[0178] The droplets may be conveyed toward the honeycomb body by a gaseous carrier stream. In one or more embodiments, the gaseous carrier stream comprises a carrier gas and an atomizing gas. In one or more embodiments, at least a portion of the carrier gas contacts the atomizing nozzle. In one or more embodiments, substantially all of the non-aqueous liquid carrier evaporates from the droplets to form agglomerates comprising particles and a binder material.
[0179] In one or more embodiments, the gaseous carrier stream is heated before mixing with the droplets. In one or more embodiments, the temperature range of the gaseous carrier stream is: greater than or equal to 50°C to less than or equal to 500°C, including all greater than or equal to 80°C to less than or equal to 300°C, greater than or equal to 50°C to less than or equal to 150°C, and all values and subranges therebetween. If the droplets collide but contain only a small amount of liquid (e.g., only contain internally), the droplets may not merge into a spherical shape. In an embodiment, non-spherical agglomerates can provide the desired filtration performance.
[0180] In one or more embodiments, the atomizing gas is heated to form a heated atomizing gas, which then flows through and / or contacts the nozzle. In one or more embodiments, the heated atomizing gas is at a temperature in the range of: greater than or equal to 50°C to less than or equal to 500°C, including all greater than or equal to 80°C to less than or equal to 300°C, greater than or equal to 50°C to less than or equal to 150°C, and all values and sub-ranges therebetween.
[0181] A carrier gas may be supplied to the apparatus to aid in drying and carrying the liquid-particle-binder droplets and the resulting agglomerates through the apparatus and into the honeycomb. In one or more embodiments, the carrier gas is primarily an inert gas, such as nitrogen. In one or more embodiments, the carrier gas consists essentially of an inert gas. In one or more embodiments, the carrier gas is primarily one or more inert gases. In one or more embodiments, the carrier gas is primarily nitrogen. In one or more embodiments, the carrier gas is primarily air. In one or more embodiments, the carrier gas consists essentially of nitrogen or air. In one or more embodiments, the carrier gas is dry. In one or more embodiments, after entering the chamber, the carrier gas contains essentially no liquid carrier. In one or more embodiments, the carrier gas contains less than 5% by weight of water vapor. In one or more embodiments, the carrier gas is heated prior to mixing with the droplets. In one or more embodiments, the carrier gas is at a temperature in the range of: greater than or equal to 50°C to less than or equal to 500°C, including all greater than or equal to 80°C to less than or equal to 300°C, greater than or equal to 50°C to less than or equal to 150°C, and all values and sub-ranges therebetween.
[0182] After the gaseous carrier stream and the liquid-particle binder droplets are intermixed in the chamber, a gas-liquid-particle-binder mixture can be formed. The gas-liquid-particle-binder mixture is heated in the intermixing zone. In one or more embodiments, during the intermixing process, droplets of liquid containing particles and binder are present. In one or more embodiments, the gaseous carrier stream is heated before intermixing with the liquid-particle-binder droplets.
[0183] Agglomerates of secondary particles or primary particles are carried in a gas flow, and when the gas passes through the honeycomb, the secondary particles or agglomerates and / or their aggregates are deposited on the inlet wall surface of the honeycomb. In one or more embodiments, the agglomerates and / or their aggregates are deposited on the porous walls of the plugged honeycomb. The deposited agglomerates can be arranged on or in the porous walls or on and in the walls at the same time. In one or more embodiments, the plugged honeycomb includes an inlet channel blocked at the far end of the honeycomb and an outlet channel blocked at the proximal end of the honeycomb. In one or more embodiments, the agglomerates and / or their aggregates are deposited on or in the walls defining the inlet channel or on and in the walls at the same time.
[0184] The flow can be driven by a fan, blower, or vacuum pump. Additional air can be drawn into the system to achieve the desired flow rate.
[0185] The average diameter of the secondary particles or agglomerates ranges from 300 nm to 10 microns, 300 nm to 8 microns, 300 nm to 7 microns, 300 nm to 6 microns, 300 nm to 5 microns, 300 nm to 4 microns, or 300 nm to 3 microns. In a specific embodiment, the average diameter of the secondary particles or agglomerates ranges from 1.5 microns to 3 microns, including about 2 microns. The average diameter of the secondary particles or agglomerates can be measured by scanning electron microscopy.
[0186] The average diameter of the secondary particles or agglomerates ranges from 300 nm to 10 microns, 300 nm to 8 microns, 300 nm to 7 microns, 300 nm to 6 microns, 300 nm to 5 microns, 300 nm to 4 microns, or 300 nm to 3 microns, including the range of 1.5 microns to 3 microns, and including about 2 microns, and the ratio of the average diameter of the secondary particles or agglomerates to the average diameter of the primary particles ranges from about 2:1 to about 67:1, about 2:1 to about 9:1, about 2:1 to about 8:1, about 2:1 to about 7:1, about 2:1 to about 6:1, about 2:1 to about 8:1, about 2:1 to about 6:1, about 2:1 to about 6:1, about 2:1 to about 6:1, about 2:1 to about 6:1. From about 2:1 to about 5:1, from about 3:1 to about 10:1, from about 3:1 to about 9:1, from about 3:1 to about 8:1, from about 3:1 to about 7:1, from about 3:1 to about 6:1, from about 3:1 to about 5:1, from about 4:1 to about 10:1, from about 4:1 to about 9:1, from about 4:1 to about 8:1, from about 4:1 to about 7:1, from about 4:1 to about 6:1, from about 4:1 to about 5:1, from about 5:1 to about 10:1, from about 5:1 to about 9:1, from about 5:1 to about 8:1, from about 5:1 to about 7:1, or from about 5:1 to about 6:1, and including from about 10:1 to about 20:1.
[0187] Depositing the agglomerates onto the porous walls may also include passing the gaseous carrier stream through the porous walls of the honeycomb, wherein the walls of the honeycomb filter filter out at least some of the agglomerates by capturing the filtered agglomerates on or in the walls of the honeycomb. In one or more embodiments, depositing the agglomerates onto the porous walls includes filtering the agglomerates from the gaseous carrier stream through the porous walls of the plugged honeycomb.
[0188] A post-treatment may optionally be used to cause the agglomerates to adhere to the honeycomb and / or to each other. That is, in one or more embodiments, at least some of the agglomerates adhere to the porous walls. In one or more embodiments, the post-treatment includes heating and / or curing the binder according to one or more embodiments (when present). In one or more embodiments, the binder material causes the agglomerates to adhere or stick to the walls of the honeycomb. In one or more embodiments, the binder material causes the agglomerates to be tacky.
[0189] In one or more embodiments, the agglomerates and / or assemblies thereof are heated after being deposited onto the honeycomb. In one or more embodiments, the heating of the agglomerates results in the removal of organic components of the binder material from the deposited agglomerates. In one or more embodiments, the heating of the agglomerates results in the inorganic components of the binder material causing the agglomerates to physically bond to the walls of the honeycomb. In one or more embodiments, the heating of the agglomerates results in the inorganic components of the binder forming a porous inorganic structure on the porous walls of the honeycomb. In one or more embodiments, the heating of the deposited agglomerates causes the organic components of the binder material to be burned off or volatilized from the deposited agglomerates.
[0190] like Fig.18 Shown is an example of an apparatus that can be used in a process for depositing an inorganic material with a binder onto a ceramic honeycomb, which can be used with the tracer particles described herein. Generally speaking, an apparatus suitable for use in the methods herein includes a conduit defining a chamber. The conduit has several sections that define different spaces and chambers. In one or more embodiments, droplets and gaseous carrier flows are passed through a conduit having an outlet end proximal to a plugged honeycomb. The conduit may include a converging section for engaging the proximal end of the honeycomb. The advantage of the converging section is that fluid convection is enhanced. During the deposition step, the conduit may be in sealed fluid communication with the plugged honeycomb. In one or more embodiments, the conduit is insulated, or substantially insulated. In some embodiments, the nozzle temperature is adjusted to achieve favorable atomization.
[0191] Fig.18 An apparatus 500 (apparatus “A”) for forming a honeycomb body is shown, the apparatus 500 comprising a conduit 551 , a deposition zone 531 , an outlet zone 536 , an outlet conduit 540 , and a flow driver 545 .
[0192] The conduit 551 spans from a first end 550 to a second end 555, defining a chamber of the conduit, which includes: an air collecting space 503 at the first end 550 and an evaporation chamber 523 downstream of the air collecting space 503. In one or more embodiments, the conduit 551 is substantially insulated. That is, the conduit 551 may not have an external heat source. The evaporation chamber 523 is defined by the evaporation section 553 of the conduit 551, which in this embodiment includes a first section 527 of non-uniform diameter and a second section 529 of substantially uniform diameter. The evaporation section 553 includes an inlet end 521 and an outlet end 525. The diameter of the first section 527 of non-uniform diameter increases from the inlet end 521 toward the section 529 of uniform diameter, which creates a divergent space occupied by the flow.
[0193] The carrier gas is supplied to the conduit 551 through the conduit 501, and the conduit 501 may have a heat source to produce the heated carrier 505. The atomizing gas 515 and the suspension 510 are separately supplied to the nozzle 520 through a separate transfer conduit (e.g., a tube or pipe), which is located at the inlet end 521 of the evaporation section 553 and is in fluid communication with the conduit 551, specifically in this embodiment, in fluid communication with the evaporation chamber 523. The suspension 510 is atomized in the nozzle 520 by the atomizing gas 515. In one or more embodiments, the suspension 510 comprises: an inorganic material, a non-aqueous liquid carrier (e.g., ethanol) and a binder, which is supplied to the nozzle as a liquid-particle-binder stream as defined herein. Through the nozzle 520, the liquid-particle-binder stream is atomized into liquid-particle-binder droplets by the atomizing gas 515.
[0194] In one or more embodiments, the heated carrier 505 flows through the nozzle 520. The atomizing gas 515 can be heated to form a heated atomizing gas. The temperature of the nozzle can be adjusted as needed.
[0195] The outlet flow from the nozzle 520 and the flow of the heated carrier 505 are both in the "Z" direction, as shown in FIG. Fig.18 As shown. There may be a diffusion region 522 downstream of the nozzle where at least some intermixing occurs. In this embodiment, the diffusion region 522 is located in the evaporation chamber 523; however, in other embodiments, the diffusion region 522 may be located in the plenum space 503, depending on the location of the nozzle.
[0196] The outlet flow from the nozzle intermixes with the heated carrier gas 505, thereby forming a gas-liquid-particle-binder mixture, which flows through the chamber of the conduit 551. Specifically, the gas-liquid-particle-binder mixture flows through the evaporation chamber 523 of the evaporation section 553 and enters the deposition area 531 at the outlet end 525 of the evaporation section 553. While intermixing, the gas-liquid-particle-binder mixture is heated inside the chamber by the heated carrier gas.
[0197] In this embodiment, the outlet flow of the nozzle enters the evaporation chamber 523 of the evaporation section 553 in substantially the same direction as the heated carrier gas. In the evaporation chamber 523, substantially all of the liquid carrier from the droplets is evaporated to form agglomerates of particles and binder material, which are interspersed in the gaseous carrier stream containing the carrier gas and the atomizing gas.
[0198] The deposition zone 531, in fluid communication with the conduit 551, houses a plugged ceramic honeycomb 530 (e.g., a wall-flow particulate filter). The deposition zone 531 has an inner diameter that is larger than the outer diameter of the ceramic honeycomb 530. To prevent leakage of the gas carrying the ceramic powder, the ceramic honeycomb 530 is sealed to the inner diameter of the deposition zone 531, a suitable seal being, for example, a gas-filled "inner tube". A pressure gauge labeled "PG" measures the pressure difference upstream and downstream of the particulate filter.
[0199] The gas-liquid-particle-binder mixture flows into the ceramic honeycomb 530, thereby depositing the inorganic material of the suspension onto the ceramic honeycomb. Specifically, the agglomerates and the gaseous carrier stream enter the honeycomb, whereby the gaseous carrier stream passes through the porous walls of the honeycomb, and the walls of the honeycomb capture the agglomerates, wherein the agglomerates and / or collections thereof are deposited onto or into the walls of the honeycomb. After post-processing of the ceramic honeycomb, the inorganic material is bonded to the ceramic honeycomb. In an embodiment, the binder material causes the agglomerates to adhere or stick to the walls of the honeycomb.
[0200] Downstream of the ceramic honeycomb 530 is an outlet zone 536 defining an outlet chamber 535. A flow driver 545 is in fluid communication with the deposition zone 531 and the outlet zone 536 downstream of the ceramic honeycomb 530 by way of an outlet conduit 540. Non-limiting examples of flow drivers are: fans, blowers, and vacuum pumps. The aerosolized suspension dries and is deposited as agglomerates of filter material onto one or more walls of the particulate filter, either as discrete areas of filter material, or in portions or, in some embodiments, as a layer (or both), wherein the agglomerates comprise primary particles of an inorganic material.
[0201] Flow through an embodiment (eg, apparatus 500) is considered to be in a downstream direction, eg, substantially parallel to the direction of gravity. In an embodiment, the apparatus is configured such that the direction of flow is in a substantially upward or vertical direction.
[0202] Embodiments of the ceramic articles herein may include a honeycomb body comprising a porous ceramic honeycomb structure including porous walls having wall surfaces defining a plurality of internal channels.
[0203] In some embodiments, the porous ceramic wall includes a material such as a filter material, which may include a porous inorganic layer disposed in some portions or, in some embodiments, on one or more surfaces of the wall. In some embodiments, the filter material includes one or more inorganic materials, such as one or more ceramics or refractory materials. In some embodiments, at least during the initial use of the honeycomb body (such as a filter after a clean state or a regenerated state of the honeycomb body) (for example, after long-term use of the honeycomb body as a filter, before significant ash and / or soot accumulation occurs inside the honeycomb body), the filter material is deposited on the wall to provide enhanced filtration efficiency (both locally through the wall and at the wall and overall through the honeycomb body).
[0204] See now Fig.19, shows a honeycomb 100 according to one or more embodiments shown and described herein. In an embodiment, the honeycomb 100 may include a plurality of walls 115 defining a plurality of internal channels 110. The plurality of internal channels 110 and the cross-channel walls 115 extend between a first end 105 (which may be an inlet end) and a second end 135 (which may be an outlet end) of the honeycomb. The honeycomb may have one or more channels that are blocked at one or both of the first end 105 and the second end 135. The pattern of blocked channels of the honeycomb is not limited. In some embodiments, the pattern of blocked and unblocked channels at one end of the honeycomb may be, for example, a checkerboard pattern, wherein alternating channels at one end of the honeycomb are blocked. In some embodiments, blocked channels at one end of the honeycomb have corresponding unblocked channels at the other end, and unblocked channels at one end of the honeycomb have corresponding blocked channels at the other end.
[0205] In one or more embodiments, the honeycomb may be formed from cordierite, aluminum titanate, enstatite, mullite, forsterite, corundum (SiC), spinel, sapphire, and periclase. In general, cordierite has a chemical formula of Mg2Al4Si5O 18 In some embodiments, the pore size of the ceramic material, the porosity of the ceramic material, and the pore size distribution of the ceramic material are controlled by, for example, changing the particle size of the ceramic raw material. In addition, a pore former may be included in the ceramic batch material used to form the honeycomb body.
[0206] See now Figure 20-21 , schematically shows a honeycomb body in the form of a particulate filter 200 .
[0207] The particulate filter 200 can be used as a wall-flow filter to filter particulate matter from an exhaust gas stream 250 (e.g., an exhaust gas stream emitted from a gasoline engine, in which case the particulate filter 200 is a gasoline particulate filter). The particulate filter 200 generally includes a honeycomb body having a plurality of channels 201 or pores extending between an inlet end 202 and an outlet end 204, defining an overall length La (e.g., Fig.21 201 of the particulate filter 200 is formed and at least partially defined by a plurality of intersecting channel walls 206 extending from an inlet end 202 to an outlet end 204. The particulate filter 200 may also include a skin layer 205 surrounding the plurality of channels 201. This skin layer 205 may be extruded during the process of forming the channel walls 206 or may be formed as a post-applied skin layer in a subsequent process, such as by applying a skin adhesive to the outer peripheral portion of the channel.
[0208] Fig.21 Shows Fig. 20208 and certain other channels are designated as outlet channels 210. In some embodiments of the particulate filter 200, at least a first group of channels may be blocked by plugs 212. Typically, the plugs 212 are disposed near the ends (i.e., the inlet ends or the outlet ends) of the channels 201. The plugs are typically arranged in a predetermined pattern, such as Fig. 20 Inlet channel 208 may be blocked at or near outlet end 204, and outlet channel 210 may be blocked at or near inlet end 202 on a channel that does not correspond to an inlet channel, such as Fig.21 Thus, each cell may be blocked at or near only one end of the particulate filter.
[0209] Fig. 20 A checkerboard plugging pattern is shown, however alternative plugging patterns may be employed in the porous ceramic honeycomb article.
[0210] In an embodiment, the honeycomb is configured to filter particulate matter from a gas stream (e.g., an exhaust gas stream from a gasoline engine). The median pore size, porosity, geometry, and other design aspects of both the bulk and the surface of the honeycomb are selected to take into account these filtering requirements of the honeycomb. For example, (may be such as Fig. 20 and 21 The walls of a honeycomb body (in the form of a particulate filter body as shown) have a filter material deposit disposed thereon, which in some embodiments is sintered by heat treatment or bonded in any other manner. The filter material deposit includes particles that are deposited on the walls of the honeycomb body and help prevent particulate matter from leaving the honeycomb body with the gas flow (e.g., soot and ash), as well as help prevent particulate matter from blocking the base portion of the walls of the honeycomb body. In this manner, and depending on the embodiment, the filter material deposit can serve as the primary filtering component, while the base portion of the honeycomb body can be configured to minimize pressure drop in any other manner, such as compared to a honeycomb body without such filter material deposit. The filter material deposit is delivered by the aerosol deposition method disclosed herein.
[0211] As discussed above, the deposited material (which may be in some parts, or in some embodiments, an inorganic layer) may be applied to the walls of the honeycomb by a method that enables the inorganic material (which may be an inorganic layer) to have a small median pore size. This small median pore size allows the material (which may be an inorganic layer) to filter out a high percentage of particulates and prevent the particulates from penetrating the honeycomb and being deposited into the pores of the honeycomb. According to embodiments, the small median pore size of the material (which may be an inorganic layer) increases the filtration efficiency of the honeycomb.
[0212] See above Fig.21 As described, the honeycomb body may have a first end and a second end. The first end and the second end are separated by an axial length "L".
[0213] According to an embodiment, the material on the wall of the honeycomb (which in some embodiments is an inorganic filter material) is thin and has porosity, and in some embodiments, also has good chemical durability and physical stability. In an embodiment, the chemical durability and physical stability of the filter material deposit on the honeycomb can be determined by subjecting the honeycomb to a test cycle including a burnout cycle and an aging test, and measuring the initial filtration efficiency before and after the test cycle. For example, an exemplary method for measuring the chemical durability and physical stability of the honeycomb includes: measuring the initial filtration efficiency of the honeycomb; loading soot onto the honeycomb under simulated operating conditions; burning off the accumulated soot at a temperature of about 650°C; subjecting the honeycomb to an aging test for 12 hours at 1050°C and 10% humidity; and measuring the filtration efficiency of the honeycomb. Multiple soot accumulation and burnout cycles can be performed. A small change in filtration efficiency (ΔFE) before and after the test cycle indicates good chemical durability and physical stability of the filter material deposit on the honeycomb. In some embodiments, ΔFE is less than or equal to 5%, for example, less than or equal to 4%, or less than or equal to 3%. In other embodiments, the ΔFE is less than or equal to 2%, or less than or equal to 1%.Determining such filtration efficiency and / or filtration efficiency changes using tracer particles as described herein may be performed.
[0214] According to one or more embodiments, a liquid suspension of an inorganic material and a binder is passed through a nozzle and, after contact with a gas stream and heating, provides a stream of aerosol particles, which are then forced into the open channels of a honeycomb. Then, a layer of inorganic material is deposited on the porous walls, with some agglomerates or inorganic material entering the pores. An off-line heat treatment process may be applied to cure the layer, which in some embodiments forms a diaphragm. According to one or more embodiments, the honeycombs manufactured and described herein (both before and after curing) exhibit significantly higher filtration efficiency and / or better FE / dP balance than bare honeycomb substrate components.
[0215] As used herein, the "clean filtration efficiency" of a honeycomb or filter article refers to a new or regenerated honeycomb that does not contain any measurable soot loading. The clean filtration efficiency of the honeycomb or filter article is greater than or equal to 70%, such as greater than or equal to 80%, or greater than or equal to 85%. In other embodiments, the initial filtration efficiency of the honeycomb or filter article is greater than 90%, such as greater than or equal to 93%, or greater than or equal to 95%, or greater than or equal to 98%.
[0216] Clean filter efficiency (at 30°C unless otherwise specified) is determined by measuring the difference between the number of particles introduced into the article and the number of particles exiting the article before and after exposure to flow conditions.
[0217] It is found that the first particles can help prevent the second particles (e.g., alumina particles) from penetrating deeply: in the absence of sacrificial particles, the penetration of the second particles will penetrate into the honeycomb wall to more than 50% of the wall thickness and into the wall; while in the case of sacrificial particles, the penetration of the second particles will be less than 25% below the wall surface, that is, less than 25% of the penetration into the honeycomb wall. Accordingly, it is found that there is a lower pressure drop for the case where the second particles do not penetrate or penetrate shallowly, as demonstrated in the examples.
[0218] There is a higher utilization of the second particle material since they are prevented from sliding through the pores at the onset of deposition.As described in the Examples, for the same amount of second suspension, higher loading of filter material (second particles) was observed with sacrificial particles.
[0219] It is obvious to those skilled in the art that various modifications and changes can be made to the embodiments described herein without departing from the spirit and scope of the subject matter claimed for protection. Therefore, this specification is intended to cover modifications and variations of the various embodiments described herein, as long as these modifications and variations fall within the scope of the attached claims and their equivalents.
Claims
1. A method of manufacturing an article, the article comprising a honeycomb structure extending axially from a first face to a second face, the structure comprising a plurality of porous walls extending axially and having a surface defining a plurality of axial channels, the walls having internal pores, wherein: The surface of the wall includes surface openings leading to at least some of the internal pores, the method comprising: axially conveying first particles from a first suspension of first particles into the channels by flowing the first particles into the honeycomb structure so that the first particles are deposited on the walls of the honeycomb structure such that at least some of the first particles are arranged in, above and / or around the surface openings, After a selected deposition amount of the first particles is deposited in the honeycomb structure, the delivery of the first particles into the channel is terminated, wherein the selected deposition amount of the first particles per volume of the honeycomb structure is greater than 0.01 g / L and less than 5.0 g / L, The first particles include sacrificial particles, the sacrificial particles include organic materials, and the organic materials include macromolecules, one or more polymers, or a combination thereof.
2. The method of claim 1, wherein: The organic material includes: protein particles, whey protein particles, collagen peptide particles, or a combination thereof.
3. The method of claim 2, wherein: The organic material comprises protein particles having a primary particle size of less than 1 μm when in suspension and a secondary or aggregate particle size of less than 10 μm after deposition onto the walls of the honeycomb structure.
4. The method of claim 1, wherein: Sacrificial particles also include calcium and phosphorus.
5. The method of claim 1, wherein: Sacrificial particles also include calcium, phosphorus, sodium and potassium.
6. The method of claim 1, wherein: Organic materials include starch.
7. The method of claim 1, wherein: Organic materials include synthetic polymers.
8. The method of claim 1, wherein: The organic material includes polystyrene, polyacrylate, oligomer, or a combination thereof.
9. The method of claim 1, wherein: Oligomers include one or more polyolefins having a molecular weight of 5000 Daltons or less.
10. The method of claim 1, further comprising: Following the flow of the first suspension, second particles are axially transferred from a second suspension of second particles into the channels, thereby depositing the second particles on the walls of the honeycomb structure, wherein the deposited sacrificial particles block at least some of the second particles from entering the interior pores of the walls.
11. The method of claim 10, wherein: The sacrificial particles block at least a majority of the second particles from entering the interior pores of the wall.
12. The method of claim 10, wherein: The sacrificial particles block all of the second particles from entering the interior pores of the wall.
13. The method of claim 10, wherein: The second particles do not penetrate below the surface of the wall by more than 25% of the lateral thickness of the wall.
14. The method of claim 10, wherein: The second particles are not arranged below the surface of the wall.
15. The method of claim 10, further comprising: After a selected deposition amount of the second particles is deposited in the honeycomb structure, delivery of the second particles into the channel is terminated, wherein the selected deposition amount of the second particles per volume of the honeycomb structure is greater than 0.01 g / L and less than 8.0 g / L.
16. The method of claim 10, further comprising: When the deposition amount of the second particles per volume of the honeycomb structure is in the range of 1.0 to 8.0 g / L, the delivery of the second particles is terminated.
17. The method of claim 10, further comprising: When the deposition amount of the second particles per volume of the honeycomb structure is in the range of 2.0 to 7.0 g / L, the delivery of the second particles is terminated.
18. The method of claim 10, further comprising: When the deposition amount of the second particles per volume of the honeycomb structure is in the range of 3.0 to 7.0 g / L, the delivery of the second particles is terminated.
19. The method of claim 10, further comprising: The honeycomb structure is heated one or more times and at one or more temperatures sufficient to remove the sacrificial particles from the honeycomb structure.
20. The method of claim 1, wherein: The first suspension includes first sacrificial particles and a carrier fluid.
21. The method of claim 20, wherein: The carrier fluid is a gas.
22. The method of claim 1, wherein: The sacrificial particles are arranged only in the parts of the internal pores of the wall having surface openings leading to the passages for the transfer of the first particles.
23. The method of claim 1, wherein: The sacrificial particles do not penetrate below the surface of the wall by more than 50% of the lateral thickness of the wall.
24. The method of claim 1, wherein: After deposition, the sacrificial particles are not arranged below the surface of the wall.
25. The method of claim 20, wherein: During the transfer of the first particles, at least some of the axial channels are blocked, thereby inducing the carrier fluid to pass through the one or more porous walls of the honeycomb structure from at least one channel to another adjacent channel.
26. The method of claim 1, wherein: At least some of the sacrificial particles bridge across at least some of the surface openings.
27. The method of claim 1, wherein: The deposition amount of the first particles per volume of the honeycomb structure ranges from 0.1 to 5.0 g / L.
28. The method of claim 1, wherein: The deposition amount of the first particles per volume of the honeycomb structure is less than 4.0 g / L.
29. The method of claim 1, wherein: The deposition amount of the first particles per volume of the honeycomb structure is less than 3.0 g / L.
30. The method of claim 1, wherein: The deposition amount of the first particles per volume of the honeycomb structure is less than 2.0 g / L.
31. The method of claim 1, wherein: The deposition amount of the first particles per volume of the honeycomb structure is 0.1 to 3.0 g / L.
32. The method of claim 1, wherein: The deposition amount of the first particles per volume of the honeycomb structure is 0.1 to 2.0 g / L.
33. The method of claim 1, wherein: The deposition amount of the first particles per volume of the honeycomb structure is 0.1 to 1.5 g / L.
34. The method of claim 1, wherein: The sacrificial particles are of a primary particle size of 0.1 to 4 μm.
35. The method of claim 1, wherein: The sacrificial particles are of a primary particle size of 0.5 to 4 μm.
36. The method of claim 1, wherein: The sacrificial particles have a median primary particle size of 0.1 μm to 3 μm.
37. The method of claim 1, wherein: The sacrificial particles have a median primary particle size of 200 μm to 600 μm.
38. The method of claim 1, wherein: The first suspension comprises one or more liquids that are prevented from coming into contact with the article.
39. The method of claim 38, wherein: Prior to contacting the article, the flow of first particles is maintained at one or more temperatures in the range of 110-160C.
40. The method of claim 1, wherein: The porous wall has a surface porosity of 35% to 75%.
41. The method of claim 1, wherein: The porous walls have a median pore size of 5 to 50 microns.
42. The method of claim 1, wherein: The porous walls have a median pore size of 5 to 30 microns.
43. The method of claim 1, wherein: The porous walls have a median pore size of 10 to 30 microns.
Citation Information
Patent Citations
Method for preparing a porous inorganic coating on a porous support using certain pore fillers
US7767256B2